Strategi Optimalisasi Hasil Akreditasi Pendidikan Pada Sekolah Menengah Pertama Swasta Darul Amin Aceh Tenggara - Faizal Luqman (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The purpose of this study is to see the quality of education services, where the implementation of accreditation policy is said guaranteed. From the sector of implementation, education is said to be of high quality if all the processes goes well according to the applicable standards. The purposes of this papers, researches want to know the optimization strategy used by SMPS Darul Amin in creating an excellent education services. This research is qualitative with descriptive survey technique. Sources of this information Principa himself , Deputy of curriculum, and several employees. The result of this study showed that SMPS Darul Amin achieved A for accreditation, were inseparable from essential factors, which is the forms of the system and values in the guise of superior school culture. Accreditation refers to the process being manipulated then has an instant impact. On the other side, the accreditation as a result from the process of creating school cultural result is far-reaching and long-last. Cultural establishment that makes it easier for members to adjust to the environment, work, and other member of organizations, helps in growing commitment and encouraging human resources to reach goals.